2012
DOI: 10.1073/pnas.1119853109
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone triggers the developmental loss of axonal regenerative capacity via thyroid hormone receptor α1 and krüppel-like factor 9 in Purkinje cells

Abstract: Neurons in the CNS of higher vertebrates lose their ability to regenerate their axons at a stage of development that coincides with peak circulating thyroid hormone (T 3 ) levels. Here, we examined whether this peak in T 3 is involved in the loss of axonal regenerative capacity in Purkinje cells (PCs). This event occurs at the end of the first postnatal week in mice. Using organotypic culture, we found that the loss of axon regenerative capacity was triggered prematurely by early exposure of mouse PCs to T 3 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 44 publications
(56 reference statements)
2
38
0
2
Order By: Relevance
“…Kruppel-like factors are increasingly recognized as important mediators of vital physiologic processes and are frequently regulated by nuclear receptors (45)(46)(47)(48). Relatively little is known about how KLF family members achieve transcriptional specificity, as the information content provided by their preferred DNA binding sequences, the CACCC box and variants (49,50), is relatively limited.…”
Section: Figmentioning
confidence: 99%
“…Kruppel-like factors are increasingly recognized as important mediators of vital physiologic processes and are frequently regulated by nuclear receptors (45)(46)(47)(48). Relatively little is known about how KLF family members achieve transcriptional specificity, as the information content provided by their preferred DNA binding sequences, the CACCC box and variants (49,50), is relatively limited.…”
Section: Figmentioning
confidence: 99%
“…These data depict a mechanism whereby FSH antagonizes sex steroid action in bone targeting osteoclasts and up-regulating bone mass accrual [65] (Figure 1). Second, prolactin (PRL), a small peptide hormone secreted by the anterior pituitary gland [66], might also directly enhance osteoclast activity, and consequently bone turnover [67][68][69] (Figure 1). Third, the primitive mammalian neurohypophyseal hormone, oxytocin (OT) [66], stimulates osteoblast differentiation by up-regulating BMP-2 expression and osteoclast formation through the activation of NF-κB and MAP kinase signaling [66] (Figure 1).…”
Section: Other Neuronal Systems Influencing Bone Mass Accrualmentioning
confidence: 99%
“…Second, prolactin (PRL), a small peptide hormone secreted by the anterior pituitary gland [66], might also directly enhance osteoclast activity, and consequently bone turnover [67][68][69] (Figure 1). Third, the primitive mammalian neurohypophyseal hormone, oxytocin (OT) [66], stimulates osteoblast differentiation by up-regulating BMP-2 expression and osteoclast formation through the activation of NF-κB and MAP kinase signaling [66] (Figure 1). Lastly, using pharmacological, genetic and in vitro assays, it was shown that argininevasopressin (AVP), a hormone secreted by the posterior pituitary gland, decreases osteoblast proliferation while increasing osteoclastic activity through its receptor Avpr1 and Avpr2 [70] (Figure 1).…”
Section: Other Neuronal Systems Influencing Bone Mass Accrualmentioning
confidence: 99%
“…De façon intéres-sante, chez les amphibiens comme le xénope, la perte de capacité régénéra-tive des neurones se produit juste après la métamorphose [4], qui est elle-même déclenchée par la T3. Dans le cadre d'un travail récemment publié dans les Proceedings of the National Academy of Sciences of USA, nous avons cherché à savoir si la T3 pouvait être impliquée dans la perte des capacités régénéra-tives axonales au cours du développe-ment d'un type de neurones, les cellules de Purkinje du cervelet [5]. Nous avons utilisé un modèle de culture organotypique, permettant d'isoler une région cérébrale tout en conservant une grande partie de la structure du tissu et les interactions cellulaires qui s'y produisent.…”
unclassified
“…Une des modulations possible de ce programme de maturation cérébrale découle de la régulation autonome du taux de T3 cérébrale. On sait, en effet, que le taux intracérébral de T3 la cellule de Purkinje [5]. Mais le rôle de la T3 dans les cellules nerveuses ne se limite pas à cette fonction, car l'hormone participe, notamment, au déclenche-ment de la myélinisation [6].…”
unclassified